THE EFFECT OF INFLATION, BANK INDONESIA RATE, NON PERFORMING FINANCING, AND COSTS OF OPERATING EXPENSES TO OPERATING REVENUES ON PROFITABILITY OF SHARIA COMMERCIAL BANKS IN INDONESIA - Syah, Toufan Aldian; Kharismasyah, Alfato Yusnar (Journal of Economicate Studies, 2018)
The Banking Industry has a very important role in economic development in a country. Indonesia, which is the largest Muslim country in the world, certainly has excellent prospects for the development of the Sharia Banking Industry in the future. Therefore, the development of Sharia banks has slowed in recent years and the profitability of Sharia banks is also still below the ideal value. This study aims to determine the internal factors and external factors that influence the profitability of Sharia Commercial Banks from January 2012 to August 2017. The variables used in this study are ROA, Inflation, NPF, and OEOR. The data used is the aggregate data of all Sharia Commercial Banks registered at Bank Indonesia. Measurement of Statistical Descriptions, F-test, t-test, Correlation Coefficient, Determination Coefficient and Multiple Linear Regression using IBM SPSS 21 software. The results showed that there were significant negative effects of the variable BI rate, NPF, and OEOR while the Inflation variable showed a negative but insignificant effect. Overall the above variables affect ROA by 87.7% while 12.3% is likely to be influenced by other factors.